Scenarios of increasing agricultural production of animal origin to cover the gaps between production and domestic availabilities of consumption, in Romania - Andreea Ion Raluca (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The purpose of this study is to identify solutions for increasing agricultural production of animal origin, with the aim of decreasing the share of imports in total supply of the market and ensuring, accordingly, a high level of food self-sufficiency. The overarching research question is: Which is the agricultural area needed to be cultivated in order to increase production to the upper limit of domestic consumption? Usually, the gap between domestic production and consumer availability is covered by imports of agricultural products and foodstuffs. Because of its negative effect upon trade balance, imports should reduce as total value and as share in total supply. This is the reason why, we suggest covering the gaps between domestic production and demand by growing the level of agricultural output, as result of increasing the area cultivated with different crops. Statistical data about structural components of food supply and demand are analysed and the area needed to obtain a higher level of production of animal origin is projected, considering the vegetable products equivalent to a physical unit of animal product. Results show that, to cover the gap between domestic consumption and production of food products of animal origin, an area of 514,339 ha of barley, oats and corn should be cultivated.
Keywords: 330; domestic availabilities of consumption; agricultural production; animal origin; imports; trade balance